O caso Fujimori: exemplo de superação da impunidade em América Latina - Barrientos-Parra, Jorge David [UNESP] (My University, 2010)
The present study focuses the impunity for human rights violations in Latin America. In this tradition of impunity, there is one exception, the emblematic case Fujimori, in which the conviction was for murder and serious injury, crimes against humanity according to the International Criminal Law. This sentence is an example in the context of this traditional trend of impunity. The research also analyzes the use of international law as a barrier state against injustice, both in substantive, imposing binding or mandatory standards with a universal character, but also in procedural terms, by providing supranational mechanisms to protect victims.

O presente estudo aborda a questão da impunidade nos casos de violações aos direitos humanos na América Latina. Nessa tradição de impunidade, surge uma exceção, o emblemático caso Fujimori, no qual ocorreu a condenação por assassinatos e lesões graves, considerados crimes contra a humanidade de acordo com o Direito Internacional Penal. Essa sentença é um exemplo em face dessa tradicional tendência de impunidade. A pesquisa analisa ainda a utilização do Direito Internacional como uma barreira contra a injustiça estatal, tanto no plano substantivo, afirmando normas vinculantes ou imperativos com caráter universal, como também no plano processual, colocando à disposição das vítimas mecanismos de proteção supranacional.
Keywords: Impunity; Latin America; International Law; Fujimori; Crimes contra a Humanidade; Direito Internacional; Direito Internacional; Fujimori